2015
DOI: 10.1097/jom.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Reconstruction and Risk Analysis for Six Semiconductor Workers With Lymphohematopoietic Cancers

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Workers in the automobile industry [ 39 ], in the sand [ 47 ] and in rubber industries [ 31 , 32 ], as well as mining workers [ 53 , 55 ] and military veterans [ 15 ] were considered in this work. Moreover, results from chemical industry studies were reported [ 18 , 21 , 25 , 33 , 35 , 41 , 49 , 54 ]. As for the activities involved, a wide variety of chemical hazards were considered in the REA assessment and are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers in the automobile industry [ 39 ], in the sand [ 47 ] and in rubber industries [ 31 , 32 ], as well as mining workers [ 53 , 55 ] and military veterans [ 15 ] were considered in this work. Moreover, results from chemical industry studies were reported [ 18 , 21 , 25 , 33 , 35 , 41 , 49 , 54 ]. As for the activities involved, a wide variety of chemical hazards were considered in the REA assessment and are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, JEMs specific to one agent has been developed by Févotte [ 27 ] to estimate of the probability and level of exposure in a general population study. A job exposure matrix for specific agents (both for chemical and physical agents), such as asphalt fume, total particulate matter, respirable crystalline silica, benzene, formaldehyde, 1,3 butadiene, as well as ionizing radiations, was also developed [ 25 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…(), benzene was not identified as a process chemical. Their decision has been criticized (Paek & Gassert, ), as previous reports have detailed the presence of benzene in the fabrication process (Jones et al., ; Paek & Gassert, ; Torres et al., ). Similarly, the exposure scenario we have assessed did not monitor benzene in the photolithography process as it was not identified as a process chemical.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of a risk assessment is to identify those risks that are significant such that alternative cost‐effective risk management options can be explored. However, exposure (a function of concentration, duration, time, and frequency) needs to be assessed through modeling, measurement, or both …”
Section: Discussionmentioning
confidence: 99%
“…However, exposure (a function of concentration, duration, time, and frequency) needs to be assessed through modeling, measurement, or both. (29) Effective occupational risk management practice is rooted in the hierarchy of controls in the preferred order of elimination, substitution, engineering control, warnings, administrative controls personal, and protective equipment. (30,31) After the implementation of effective controls, what remains is "residual" or insignificant risk and can be thought of as a "safe level."…”
Section: Discussionmentioning
confidence: 99%